2020
DOI: 10.1111/aas.13732
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mean systemic filling pressure and acute kidney injury: An observational cohort study following cardiac surgery

Abstract: Background Venous congestion has been implied in cardiac surgery‐associated acute kidney injury (CSA‐AKI). The mean systemic filling pressure may provide a physiologically more accurate estimate of renal venous pressure and renal perfusion pressure but its association with CSA‐AKI has not been reported. Methods Patients admitted to ICU following cardiac surgery without pre‐operative renal dysfunction were included with monitoring of mean arterial pressure (MAP) and central venous pressure (CVP) and cardiac out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Greater relative hypotension was caused by higher preoperative or lower postoperative MPP, while smaller relative hypotension was caused by lower preoperative or higher postoperative MPP. Since previous studies [ 16 , 17 , 38 ] and our study have consistently shown that lower postoperative MPP is a risk factor of AKI, the non-linear relationship between preoperative MPP and AKI progression could weaken the association between relative hypotension and AKI progression. Higher preoperative MPP could increase the risk of AKI due to the right shift in the lower pressure limit of renal autoregulation in the presence of chronic hypertension [ 14 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Greater relative hypotension was caused by higher preoperative or lower postoperative MPP, while smaller relative hypotension was caused by lower preoperative or higher postoperative MPP. Since previous studies [ 16 , 17 , 38 ] and our study have consistently shown that lower postoperative MPP is a risk factor of AKI, the non-linear relationship between preoperative MPP and AKI progression could weaken the association between relative hypotension and AKI progression. Higher preoperative MPP could increase the risk of AKI due to the right shift in the lower pressure limit of renal autoregulation in the presence of chronic hypertension [ 14 ].…”
Section: Discussionmentioning
confidence: 55%
“…Mean perfusion pressure (MPP), which is the difference between MAP and central venous pressure (CVP), can also be used as a surrogate marker for renal perfusion because elevated CVP has been reported as a risk factor for AKI in ICU patients [ 13 , 14 ]. Although CVP monitoring is readily available in patients after cardiac surgery [ 15 ], few studies have assessed the relationship between MPP and AKI in this population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the difference in Pmsf − CVP between 48 hours and the time of admission was positively correlated with total negative uid balance at 48 hours, suggesting a gradual decrease in the differential venous return driving pressure in patients with negative uid balance. Regarding the relationship between venous return and organ function, a study comparing MAP − CVP and MAP − Pmsf found that MAP − Pmsf correlated better with acute kidney injury and better represented the backward pressure of renal perfusion pressure [43]. Pmsf is an upstream indicator of venous return.…”
Section: Discussionmentioning
confidence: 99%
“…With a great interest we read the recent article by Neuman et al 1 assessing the association between mean systemic filling pressure analogue (P msa ) and acute kidney injury (AKI) following cardiac surgery. They showed that P msa as a surrogate for renal venous pressure was more closely associated with postoperative AKI than central venous pressure.…”
Section: Sirmentioning
confidence: 99%